First study on waterbirds wintering at the southern Mekhada marsh (North-East Algerian Ramsar site) - Bourafa, Y; Boucheker, A; Seddik, S. (My University, 2018)
The phenology of waterbirds was carried out in the south of the Mekhada marsh an important birds area (IBA) in the North-East of Algeria during two wintering seasons (2015-2016 and 2016-2017). We used a Optolyth telescope with 20-80X zoom, to conduct regular censuses of waterbirds in the studied area. In total, 40 species representing 12 families were recorded at this site. In winter, Ducks are well represented (10 species, with a maximum of 26835 and 33875 individuals were counted in January and February through the two wintering periods). The results of ecological indices (Shannon and equitability) and species richness showed an imbalance in the stand of waterbirds dominated by three families (Anatidae, Scolopacidea and Rallidea). We noted an increase in frequentation on the study area among the two wintering seasons (2 test = 360, 12; df = 1; p = 0, 0001). The correspondence factor analysis showed three distinct periods representing (The beginning, middle and end of wintering season). This preliminary results, of wintering waterbirds monitoring showed that the Mekhada marsh seems to offer ideal conditions for wintering and resting migratory waterbirds.